El Plan Colombia y su influencia en la subregión andina - Tello Vidal, Luis Ernesto (2005)
This essay explores Colombian conflict from its origins to nowadays. Different stages of solutions proposing the establishment of two forums are studied: first, inside Colombia, formed by members of the civil society. Second, an international forum considering the experience of ‘Contadora Group’ (twenty years ago) with member countries of the Andean Community where drug production is massive, which are included in the Andean Regional Initiative (American strategic of fight against illegal traffic in drugs); the countries of the recently born South American Community of Nations; and in the other hand, the United States and the European Union as countries which receive the biggest amount of drug production from the Andean area.